2011
DOI: 10.1111/j.1365-2966.2011.19381.x
|View full text |Cite
|
Sign up to set email alerts
|

How active galactic nucleus feedback and metal cooling shape cluster entropy profiles

Abstract: Observed clusters of galaxies essentially come in two flavours: non‐cool‐core clusters characterized by an isothermal temperature profile and a central entropy floor, and cool‐core clusters where temperature and entropy in the central region are increasing with radius. Using cosmological resimulations of a galaxy cluster, we study the evolution of its intracluster medium (ICM) gas properties, and through them we assess the effect of different (subgrid) modelling of the physical processes at play, namely gas co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
73
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(79 citation statements)
references
References 77 publications
(140 reference statements)
6
73
0
Order By: Relevance
“…Upon closer inspection one notices that a similar but slightly weaker offset also exists in the power-law part of the entropy profile, where the simulated profiles are systematically offset to lower entropy. A similar discrepancy can be seen also, e.g., in Figure 7 of Dubois et al (2011), independently of the much larger range of subgrid models employed in that reference. This may point towards additional physics missing from these simulations.…”
Section: Comparison With Icm Profiles From X-ray Datamentioning
confidence: 69%
“…Upon closer inspection one notices that a similar but slightly weaker offset also exists in the power-law part of the entropy profile, where the simulated profiles are systematically offset to lower entropy. A similar discrepancy can be seen also, e.g., in Figure 7 of Dubois et al (2011), independently of the much larger range of subgrid models employed in that reference. This may point towards additional physics missing from these simulations.…”
Section: Comparison With Icm Profiles From X-ray Datamentioning
confidence: 69%
“…Only recently fully cosmological grid simulations have reached a sufficient dynamical range to model the evolution and feedback of AGN outflows in detail, studying the interplay between AGNs and the ICM (e.g. Xu et al 2009;Teyssier et al 2011;Dubois et al 2011;Kim et al 2011). Recently, the outflows from AGNs in the multiphase ICM has been simulated in detail with FLASH simulations by Gaspari et al (2012a,b).…”
Section: Agn Outflows In Cluster Coresmentioning
confidence: 99%
“…Numerical simulations have demonstrated that AGNs may be important sources of feedback energy and significantly impact the energy balance in clusters. Simulations show that AGNs bring simulations closer to observations by preventing overcooling, which lowers cluster central densities (Sijacki et al 2007;Short & Thomas 2009;Teyssier et al 2011;Dubois et al 2012), improves the distribution of metals (Fabjan et al 2010;McCarthy et al 2010;Dubois et al 2011), and regulates star formation rates and triggers quenching (Di Matteo et al 2005;Sijacki & Springel 2006).…”
Section: Introductionmentioning
confidence: 99%